Comparison of Tuberculosis Examination Using Ziehl-Neelsen Method and Molecular Rapid Test - Anwar, Aan Yulianingsih; Handayani, Marini Tri Putri; Nurdin, Erpi; Lewa, Irma Berliana,HI; Artati, Artati (Jurnal Kesehatan Manarang, 2023)
Tuberculosis is an infectious disease of the respiratory tract caused by infection with the bacteria Mycobacterium tuberculosis. Fast and accurate diagnostic methods are very important for diagnosing and controlling pulmonary TB disease in Indonesia. TB examination using the Zn method is very commonly used even though it has lower sensitivity than TCM. The aim of this study was to compare the results of TB examination using BTA staining with the Molecular Rapid Test. This type of research uses analytical observational methods with a cross-sectional approach. The sample was 40 respondents taken using purposive sampling technique. The results of tuberculosis examination using the Ziehl-Neelsen (ZN) BTA staining method and the Moluker rapid test tool (TCM) method showed that the microscopic results of the Ziehl-Neelsen method of BTA smear staining showed negative results in 31 people (75%), 1 respondent (2 .5%) with scanty results and 9 respondents (22.5%) with 1+ results. The results of the TB BTA examination using the TCM method resulted in MTB Not Detected with a total of 30 people (75%), MTB Detected Medium obtained a result of 6 people (15%), MTB Detected Low obtained a result with a total of 3 people (7.5%), MTB Detected Very Low results were obtained with the number of 1 person (2.5%) and in the SPSS results using the t-test the results obtained were p value <0.05 (0.012 <0.05) which means there is a comparison of the BTA staining tuberculosis examination using the Ziehl-Ziehl method. neelsen and Molecular Rapid Tests. Based on the research results, it was found that there was a significant difference between the Ziehl-Neelsen BTA staining tuberculosis examination method and the Molecular Rapid Test Tool with a p value <0.05 (0.012 <0.05)